2006
DOI: 10.1007/s10641-006-9159-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective predation by four darter (Percidae) species on larval chironomids (Diptera) from a Mississippi stream

Abstract: We determined seasonal foraging modes of four sympatric darter species, Etheostoma lynceum, E. stigmaeum, E. swaini and Percina nigrofasciata, from Beaverdam Creek, Mississippi (USA) at two scales of taxonomic resolution: (1) chironomid prey identified to family and (2) chironomid prey identified to genus/species. When chironomids were identified to family, high proportional similarity (PS) and low niche breadth (NB) values suggested the darters fed opportunistically on a relatively small number of available p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
3
9
0
1
Order By: Relevance
“…While diets of riverine fish predators were more diverse based on metabarcoding analysis than morphological diet analysis of these species has previously recorded, the identities of the most prevalent prey items were largely consistent with previous dietary observations of the particular predator species in this study. Three darter species sampled in the UBR (logperch, blackside darter, and rainbow darter) preyed primarily on mayfly (ESUs: Baetidae, Ephemerelloidea, and Other Ephemeroptera) and midge larvae (Families: Chironomidae and Simuliidae), which is similar to the findings of previous studies (Alford & Beckett, ; Phillips & Kilambi, ). Pumpkinseed sunfish [ Lepomis gibbosus (Linnaeus, 1758)] appeared to specialize on mollusks, snails (Order: Panpulmonata) and clams (Infraclass: Euheterodonta), along with smaller contributions to the diet from other benthic invertebrates and cyprinids, all of which have been observed in other systems (García‐Berthou & Moreno‐Amich, ; Locke, Bulté, Forbes, & Marcogliese, ; Mittelbach, ).…”
Section: Discussionsupporting
confidence: 87%
“…While diets of riverine fish predators were more diverse based on metabarcoding analysis than morphological diet analysis of these species has previously recorded, the identities of the most prevalent prey items were largely consistent with previous dietary observations of the particular predator species in this study. Three darter species sampled in the UBR (logperch, blackside darter, and rainbow darter) preyed primarily on mayfly (ESUs: Baetidae, Ephemerelloidea, and Other Ephemeroptera) and midge larvae (Families: Chironomidae and Simuliidae), which is similar to the findings of previous studies (Alford & Beckett, ; Phillips & Kilambi, ). Pumpkinseed sunfish [ Lepomis gibbosus (Linnaeus, 1758)] appeared to specialize on mollusks, snails (Order: Panpulmonata) and clams (Infraclass: Euheterodonta), along with smaller contributions to the diet from other benthic invertebrates and cyprinids, all of which have been observed in other systems (García‐Berthou & Moreno‐Amich, ; Locke, Bulté, Forbes, & Marcogliese, ; Mittelbach, ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, even fewer diet studies have identified chironomid larvae to the genus/species level. We believe that, in addition to a systematic assessment of prey availability, identifying chironomid larvae to genus helps to accurately determine foraging mode for suctionfeeding, benthic invertivores (Alford and Beckett 2007), especially when larval chironomids are consumed so disproportionately to other families of prey items.…”
Section: Discussionmentioning
confidence: 99%
“…Following the methods of Alford and Beckett (2007), foraging mode was determined by comparing the relative abundances (i.e., percent composition by number) of invertebrate taxa in the gut contents of all lake sturgeon combined by season to the relative abundances of the same invertebrate taxa collected from the resource base. The resource bases sampled included benthic sediment predominately composed of silt and clay and hard artificial substrates from rock cages.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Contrasting NB values (especially between F. stellifer and N. xaenocephalus) provide further evidence of this selective feeding. The high number of Chironomidae in the diet of F. stellifer may also be explained by densities often >50,000 Chironimidae/m 2 in aquatic environments (Coffman and Ferrington 1996), making them the most abundant food resource available and the bulk of the diet of most stream fi shes (Alford andBeckett 2007, Matthews et al 1982). The signifi cant relationship between weight of gut contents and SL suggests that the amount of food consumed increases with size.…”
Section: Discussionmentioning
confidence: 99%